2020
DOI: 10.20546/ijcmas.2020.903.119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Germplasm Accessions for Drought Tolerance in Green gram [Vigna Radiata (L.)]

Abstract: Among pulse crops, green gram is an important annual legume grown principally for its high protein seeds that are used as human food (Singh et al., 1988). The wild mung bean progenitor of present day cultivated species is widely distributed in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
3
0
0
Order By: Relevance
“…These results conformed with the findings of Azam et al [11]. Similar substantial variations in the yield and other aspects were observed by Kanavi et al [43].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results conformed with the findings of Azam et al [11]. Similar substantial variations in the yield and other aspects were observed by Kanavi et al [43].…”
Section: Discussionsupporting
confidence: 93%
“…It may be revealed that there exists significant genetic diversity among the genotypes based on the distribution pattern of the genotypes on the biplot. Similar results for grouping a large number of green grams among genotypes by a variable biplot have been published by Kanavi et al [ 43 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation